Philosophical and Anthropological Vision of the Idea of Spirituality in Isaac Asimov’s Foundation Trilogy - Kostiuchkov, S. K.; Vorobiova, A. V. (Anthropological Measurements of Philosophical Research, 2024)
Purpose. The article is a philosophical and anthropological representation of the idea of spirituality in The Foundation Trilogy by the American science fiction writer, philosopher, populariser of science Isaac Asimov. Theoretical basis. The study is based on an understanding of the worldview imperatives of Asimov’s work, which highlight his philosophical and anthropological vision of spirituality as a historically established property of a rationally organised society and a key condition for its progressive evolution. The emergence, stochasticity and eventuality of the development of the modern global society brings the content of A. Azimov’s philosophical and anthropological ideas to a fundamentally new level of understanding of the further development of humanity. Asimov’s articulation of the idea of spirituality in The Foundation Trilogy allows us to define the philosophical and anthropological concept of the writer in the fullness of its social, philosophical, existential and axiological dimensions. Originality. The authors have substantiated the expediency and relevance of considering the idea of spirituality in A. Asimov’s Foundation trilogy in the semantic field of philosophical anthropology. It is shown that Asimov’s philosophical anthropology has a clearly expressed teleological "load". In the writer’s interpretation, a person of the future is not a "posthuman" with a biological nature altered by special technologies, but a person focused on spiritual development and self-improvement based on the eternal values enshrined in the mental code of Homo sapiens – happiness, love, freedom, dignity, independence, patriotism. Conclusions. Foundation is a multifaceted work, rich in plot, compositionally mosaic and polyphonic, in which, at first glance, it is difficult to identify any dominant idea. In the course of the study, it was found that one of the main content centres in A. Asimov’s works is the philosophical and anthropological discourse, in the space of which considerable attention is paid to human spirituality.